Electromagnetic compatibility of high voltage substation SMART devices - B. R. Kangozhin; M. S. Zharmagambetova; S. S. Dautov; D. E. Elubaev (Physical Sciences and Technology, 2021)
The article presents the results of a study of the electromagnetic compatibility of SMART devices (SD) ofautomated technological control systems (ATCS) at a high voltage electrical substation. The interferenceimmunity of relay protection and automation devices associated with the use of electrical control cableshas been investigated. Possible sources of pulsed radiated noise at the electrical substation are listed. Thelevels of pulsed electromagnetic noise at the 220 kV Karatau substation of KEGOC JSC were determinedby the calculation and experimental method, which in some cases exceeded the noise immunity of theinstalled ATCS devices. An experimental method for determining the actual shielding coefficients ofcontrol cables at an electrical substation is presented, as well as the measurement results. The influence ofshielding of relay cables on the level of electromagnetic influences on SD is revealed. Possible levels ofradiated interference were determined, taking into account the screening factor of existing control cables,and the need to replace control cables was argued